Retrospective study of correlation between high risk detection of HPV and liquid based cervical cytology for cervical cancer screening - Thakur, Niki; Aryal, Gopi; Rana, Reena (Nepal Mediciti Medical Journal, 2024)
BACKGROUND Cervical cancer is most common in Nepalese women. Human papilloma virus (HPV) plays a main role in pathogenesis of cervical cancer. Human papilloma virus serotype 16 is the most common type followed by HPV 18. Liquid based smear cytology (LBC) is a simple, safe, non-invasive and cost effective method for the detection of squamous intraepithelial lesion or squamous cell carcinoma. The aim of this study was to correlate HPV DNA testing result with the findings of Liquid based cytology. METHODS This was a retrospective study conducted for 2 years at Department of Laboratory Medicine Pathology, Nepal Mediciti hospital from 1st may 2021 to 30th April 2023. Total of 1456 cases were included in this study. RESULTS Out of 1456 cases, 100 cases were positive for HPV. The concordance between HPV DNA test and LBC findings is 57%. The highest HPV-positive cases were seen in the age group of 31-40years. The most common HPV genotype study was HPV 16 (28%) followed by HPV 18 (27%). HPV 16 was positive in 57% of ASCUS positive cases of LBC, is statistically significant (P value-0.017). HPV 18 was positive in 37.0% of ASCUS positive cases of LBC, is not statistically significant (P value-0.018). The concordance between HPV positive detection and LBC findings is 57% and discordance is 43%. CONCLUSIONS This study shows the prevalence of HPV is higher in middle to young age group. ASCUS was common finding in LBC in HPV positive cases followed by LSIL,HSIL and SCC. However 43% of HPV positive cases were reported as negative for intraepithelial lesion (NILM) as there was no abnormality in squamous epithelial cells. Both the HPV test and cervical LBC smears are valuable tools for early detection of cervical precursor lesion. However, neither test alone provides conclusive results for comprehensive screening. So, it is recommended to use both test in combination for more accurate and reliable findings in cervical cancer screening.